The Impact of High Dietary Sodium Consumption on Blood Pressure Variability in Healthy, Young Adults. (1st February 2020) - Migdal, Kamila U; Babcock, Matthew C; Robinson, Austin T; Watso, Joseph C; Wenner, Megan M; Stocker, Sean D; Farquhar, William B
Abstract: BACKGROUND: High sodium (Na + ) intake augments blood pressure variability (BPV) in normotensive rodents, without changes in resting blood pressure (BP). Augmented BPV is associated with end-organ damage and cardiovascular morbidity. It is unknown if changes in dietary Na + influence BPV in humans. We tested the hypothesis that high Na + feeding would augment BPV in healthy adults. METHODS: Twenty-one participants (10 F/11 M; 26 ± 5 years; BP: 113 ± 11/62 ± 7 mm Hg) underwent a randomized, controlled feeding study that consisted of 10 days of low (2.6 g/day), medium (6.0 g/day), and high (18.0 g/day) salt diets. On the ninth day of each diet, 24-h urine samples were collected and BPV was calculated from 24-h ambulatory BP monitoring. On the tenth day, in-laboratory beat-to-beat BPV was calculated during 10 min of rest. Serum electrolytes were assessed. We calculated average real variability (ARV) and standard deviation (SD) as metrics of BPV. As a secondary analysis, we calculated central BPV from the 24-h ambulatory BP monitoring. RESULTS: 24-h urinary Na + excretion (low = 41 ± 24, medium = 97 ± 43, high = 265 ± 92 mmol/24 h, P < 0.01) and serum Na + (low = 140.0 ± 2.1, medium = 140.7 ± 2.7, high = 141.7 ± 2.5 mmol/l, P = 0.009) increased with greater salt intake. 24-h ambulatory ARV (systolic BP ARV: low = 9.5 ± 1.7, medium = 9.5 ± 1.2, high = 10.0 ± 1.9 mm Hg, P = 0.37) and beat-to-beat ARV (systolic BP ARV: low = 2.1 ± 0.6, medium = 2.0 ± 0.4, high = 2.2 ± 0.8 mm Hg, P = 0.46) were not different. 24-h ambulatory SD (systolic BP: P = 0.29) and beat-to-beat SD (systolic BP: P = 0.47) were not different. There was a trend for a main effect of the diet ( P = 0.08) for 24-h ambulatory central systolic BPV. CONCLUSIONS: Ten days of high sodium feeding does not augment peripheral BPV in healthy, adults. CLINICAL TRIALS REGISTRATION: NCT02881515.